1995
DOI: 10.1002/j.1550-8528.1995.tb00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure in Lean and Obese Prepubertal Children

Abstract: DELANY, JAMES P, DAVID W HARSHA, JAMES C KIME, JULffi KUMLER, LOUIS MELANCON AND GEORGE A BRAY. Energy expenditure in lean and obese prepubertal children. Obes Res. 1995;3[suppl1]:67-72.The relationship between energy expenditure and obesity was examined in prepubertal children. Consenting fifth graders underwent Tanner Staging, weight, height and skinfold measurements. Subjects were selected for further study to obtain equal numbers of girls and boys with a wide range of body composition. Weight, total daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Our ®ndings of no differences between the groups after adjusting for body composition, agree with previous investigators 11,14,15,29 despite differences in study design and methodology. Two cross-sectional studies 11,29 examined the relationship between EE vs fatness in infants and children, and reported no relationships between TEE, BMR or activity EE and fatness in children or fatness in parents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our ®ndings of no differences between the groups after adjusting for body composition, agree with previous investigators 11,14,15,29 despite differences in study design and methodology. Two cross-sectional studies 11,29 examined the relationship between EE vs fatness in infants and children, and reported no relationships between TEE, BMR or activity EE and fatness in children or fatness in parents.…”
Section: Discussionsupporting
confidence: 92%
“…10±13 A low physical activity EE, only 16.7% of TEE, was reported in children aged 5 y. 10 Two studies comparing obese and nonobese children have reported no signi®cant differences in TEE (measured by DLW), physical activity EE or PAL in either prepubertal children 14 or adolescents. 15 However, both studies suggested that the obese children had a reduced activity level.…”
Section: Introductionmentioning
confidence: 99%
“…Several crosssectional studies in pre-pubertal children have shown that energy expenditure, including physical activity energy expenditure, is similar in lean vs obese children, especially after controlling for differences in body composition. 91,92 Children of obese vs lean parents have also been examined as a model of`preobesity'. One study showed that children of obese parents had a reduced energy expenditure, including physical activity energy expenditure, 93 whereas another study did not.…”
Section: Physical Activity and Obesitymentioning
confidence: 99%
“…8 Previous research on physical activity in paediatric obesity has focused on non-clinical samples, comparing habitual physical activity or energy expenditure in obese and nonobese children and adolescents. [9][10][11][12][13][14][15][16] Most of these studies found lower levels of physical activity and *PAL (TEE/REE) in obese children and adolescents relative to their lean counterparts. [9][10][11][12][14][15][16] The few studies that have compared objec-tively measured sedentary behaviour in non-clinical samples of obese and lean children have reported inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Most of these studies found lower levels of physical activity and *PAL (TEE/REE) in obese children and adolescents relative to their lean counterparts. [9][10][11][12][14][15][16] The few studies that have compared objec-tively measured sedentary behaviour in non-clinical samples of obese and lean children have reported inconsistent results. 10,14,15 The aims of this study were therefore to use accelerometry to (1) measure habitual physical activity and sedentary behaviour objectively in a clinical sample of obese children aged 5-11 years; (2) compare the results with a sample of ageand sex-matched non-obese control children.…”
Section: Introductionmentioning
confidence: 99%